Employment motivation of airline pilots in the USA. (2016) - Byrnes, Kenneth P.; Brady, Tim
The airline industry is currently experiencing a high volume of airline pilot retirements. As a result, there is a large demand for new airline pilots. Many regional airlines are reporting that there is a pilot shortage in the airline industry since they are having difficulty hiring enough qualified pilots to meet their demand. Conversely, research has shown that there is a sufficient number of qualified pilots in the USA to meet the current and future demand. The purpose of this descriptive study was to quantify the motivations of the entire ATP/commercial pilot population and to specifically identify the reasons why two-thirds of the ATP/commercial pilot population have decided not to seek airline employment. The results suggest that insufficient pay is the primary reason that pilots choose non-aviation careers and that an increase in starting salary would motivate many qualified pilots to seek employment at regional airlines.